A new mesitylenic cyclobutane substituted Schiff base ligand and its Co(II), Cu(II), Ni(II), and Zn(II) complexes - Çukurovali, A; Yilmaz, I; Özmen, H; Ahmedzade, M (John Wiley & Sons Inc, 2001)
A new ligand, 4-(1-methyl-1-mesityl-3-cyclobutanyl)-2-(2-hydroxy-1-naphthylideneimino) thiazole (LH), has been synthesized starting from 1-methyl-1-mesityl-3-(2-chloro-1-oxoethyl)cyclobutane and thiourea and subsequently 2-hydroxy-1-naphthalaldehyde. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II), Ni(II), and Zn(II) metals. The authenticity of the ligand and its complexes ave proposed based on elemental analyses, IR, UV-vis, C-13 and H-1 NMR spectra, magnetic susceptibility measurements, thermogravimetric analyses, and differential scanning calorimetry. (C) 2001 John Wiley & Sons, Inc.